Sosialisasi dan Pendampingan Materi Pembelajaran IPA Berbasis Metakognisi pada Mahasiswa Magister Pendidikan IPA Universitas Mataram - Wildan Wildan; Dwi Laksmiwati; I Nyoman Loka; Supriadi Supriadi (Pendidikan Matematika, FKIP Universitas Mataram, 2021)
Community service activities have been carried out for master students of Science Education at the University of Mataram which aimed to provide understanding to students about the development of science teaching materials that can develop students' metacognition. Teaching materials that are able to develop metacognitive abilities are needed by students in the current era of globalization. With the ability of metacognition, it will raise students' awareness of what they really know and one's cognition-regulation functions to regulate their cognitive activities effectively. Knowledge-cognition contains declarative, procedural, and conditional knowledge, while metacognition skills include four skills, namely problem solving skills, decision-making skills, critical thinking skills, and creative thinking skills. Activity participants can understand the material presented which was shown by the ability to answer questions during the discussion. An understanding of proper metacognition was also measured by its ability to fill out a questionnaire that was distributed after the service was complete. A good understanding of metacognition is expected to be a guide in developing metacognition-based teaching materials so that students can develop metacognition abilities.